A Randomized Controlled Trial Evaluating the Effectiveness of a Short Video-Based Educational Program for Improving Mental Health Literacy Among Schoolteachers - Ueda, Junya; Yamaguchi, Satoshi; Matsuda, Yasuhiro; Okazaki, Kosuke; Morimoto, Tsubasa; Matsukuma, Seiya; Sasaki, Tsukasa; Kishimoto, Toshifumi (Frontiers in Psychiatry, 2021)
Background: Mental illness-related stigma represents a barrier to seeking and receiving appropriate mental health care. Mental health literacy (MHL) can improve mental health knowledge, decrease stigmatizing attitudes, and enhance help-seeking behavior. Starting from 2022, mental illness-related education was set to be introduced in high schools in Japan. For this current situation, we conducted a parallel group, randomized controlled trial to examine the effectiveness of MHL educational program for teachers. Methods: The educational program described in this study comprised a 50-minute video lesson designed to improve teachers’ MHL. All participants were schoolteachers and were assigned either to an educational group or a waitlist control group. The assessment was conducted for both groups twice: first at baseline and then at one-hour post-intervention. The outcome measures for this trial are changes in knowledge, attitudes, and intended behaviors. Results: The educational group showed a greater improvement in knowledge regarding mental health than the control group did. The program was not effective for decreasing stigma toward mental illness. However, the educational group showed an increased intention to assist students with depression. Limitations: No long-term follow-up was implemented, which means the persistence of the educational program’s effect could not be determined. Further, we could not report whether the program induced a change in teachers’ behaviors regarding providing support for their students. Conclusions: The short video-based MHL educational program can improve schoolteachers’ MHL and increase their intention to assist students. These findings can help in the development of similar educations in countries/regions experiencing similar issues regarding mental health.